IMPROVING STUDENTS’ WRITING ABILITY BY USING DICTATION METHOD OF DESCRIPTIVE TEXT AT GRADE 7 SMP MAYJEND SUTOYO SM MEDAN - Silaban, Friska Hotrauli; Hanim, Saidatul (English Language Teaching Prima Journal (ELT), 2023)
This research was conducted with the aim of elucidating the “improving students’ writing ability by using dictation method of descriptive text. The purpose of this study is to analyze students’ writing ability by using dictation method of descriptive text. This research was conducted at SMP Mayjend Sutoyo SM Medan. There were 25 students in class VII. This study is used a writing test instrument. There were 10 questions that the researchers gave tp grade 7 students from and after the dictation activity of descriptive text.This can be seen from the average student score answer was 51.6% Yes and 48.4% No. This indicates a change in attitude after learning with the dictation method. Interestingly, students expressed a preference for the dictation method because it was considered to facilitate writing descriptive texts, improve focus, and instill joy in the writing process. Overall, the pretest, observation, interview, and posttest results provided a comprehensive overview of the initial challenges, developments during learning, and changes in students' attitudes toward the dictation method. Despite facing initial uncertainty and difficulties, the dictation method proved to be an effective approach in enhancing students' understanding and interest in writing descriptive texts.